2012
DOI: 10.1007/s00253-012-4551-9
|View full text |Cite
|
Sign up to set email alerts
|

New strategies for drug discovery: activation of silent or weakly expressed microbial gene clusters

Abstract: Genome sequencing of Streptomyces, myxobacteria, and fungi showed that although each strain contains genes that encode the enzymes to synthesize a plethora of potential secondary metabolites, only a fraction are expressed during fermentation. Interest has therefore grown in the activation of these cryptic pathways. We review current progress on this topic, describing concepts for activating silent genes, utilization of “natural” mutant-type RNA polymerases and rare earth elements, and the applicability of ribo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
225
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(233 citation statements)
references
References 99 publications
(132 reference statements)
4
225
0
4
Order By: Relevance
“…In addition to these targeted approaches, a whole array of more pleiotropic strategies can be applied in order to activate silent gene clusters: for instance microbial co‐cultivation; addition of rare earth elements or nutrition signals, such as the cell wall metabolite N‐acetylglucosamine; or application of stress conditions (e.g. ethanol or heat stress treatment) have successfully been show to elicit silent gene cluster expression (Ochi and Hosaka, 2013; Abdelmohsen et al ., 2015; Rutledge and Challis, 2015). Altogether, this allows to exploit the natural product producers more intensively as it has been possible in the years before and will lead to the identification of quite a number of new secondary metabolites in the near future.…”
Section: Novel Approaches For Drug Discoverymentioning
confidence: 99%
“…In addition to these targeted approaches, a whole array of more pleiotropic strategies can be applied in order to activate silent gene clusters: for instance microbial co‐cultivation; addition of rare earth elements or nutrition signals, such as the cell wall metabolite N‐acetylglucosamine; or application of stress conditions (e.g. ethanol or heat stress treatment) have successfully been show to elicit silent gene cluster expression (Ochi and Hosaka, 2013; Abdelmohsen et al ., 2015; Rutledge and Challis, 2015). Altogether, this allows to exploit the natural product producers more intensively as it has been possible in the years before and will lead to the identification of quite a number of new secondary metabolites in the near future.…”
Section: Novel Approaches For Drug Discoverymentioning
confidence: 99%
“…They mapped the mutation to a ribosomal protein and showed that only the mutant ribosome led to activation of the silent Act gene cluster (act), thus demonstrating translational control in Act biosynthesis. The method has been extended to other antibiotics and many successful applications have followed (Ochi 2007;Ochi and Hosaka 2013). Ochi and Hosaka (2013) have recently provided a comprehensive summary of the applications of ribosome engineering.…”
Section: Motivationmentioning
confidence: 99%
“…The method has been extended to other antibiotics and many successful applications have followed (Ochi 2007;Ochi and Hosaka 2013). Ochi and Hosaka (2013) have recently provided a comprehensive summary of the applications of ribosome engineering. Here we focus on the original studies that provided the impetus for the field as well as a molecular rationale for ribosome engineering.…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many approaches, including isolation of mutants altered in transcription or translation, genetic manipulation of positive and negative regulation, heterologous expression in specialized hosts and others, have been described. 8,[21][22][23][24][25][26][27][28][29][30] For microbial genome mining to become a robust methodology to drive the discovery of new and novel NPs for drug discovery, it is important to have a set of bioinformatics tools that can predict which microorganisms are the most 'gifted' for SM production. antiSMASH 3.0 31 is particularly useful to identify the numbers and types of SMs encoded by microbes, and has been used to survey a wide range of bacteria and archaea for those microorganisms most gifted for SM production.…”
Section: Introductionmentioning
confidence: 99%